(untitled) (Jurnal Intek Akuakultur, 2020)
The purpose of this research was to determine the effect of papaya leaf extract (Carica papaya L) to combat of Vibrio sp. green colony population on both media and shrimp body (Litopenaeus vannamei). This research was conducted in July-August 2018 at PT. SyAqua Indonesia Serang, Banten. This research used Completely Randomized Design (CRD) with treatments consisted of papaya leaf extract concentration that were 30 mg/L, 45 mg/L and 0 mg/L as control. Parameters observed during the study were shrimp survival rate, water quality (pH, temperature, salinity, ammonia and alkalinity), profile of bacterial density consisted of total bacterial Vibrio sp., total green colony, total yellow colony and ratio green colony on total bacterial. The result showed that the addition of papaya leaf extract more able to combat bacterial population comparing with control. The higest concentration, 45 mg/L was given the best protection from vibriosis with survival rate until 22,5% while control just 9,5% and other 18,6%. Water quality parameters during maintenance still in a state of optimum range.